Contaminant Removal in Soil and Wash Water Residue from Ex-Mining Area in Jambi using Soil Washing Remediation - Hadrah, Hadrah; Anggrika Riyanti; Kasman, Monik; Arrasyid, M. Aderiansyah; Istigmah, Nuni (Journal of Smart Agriculture and Environmental Technology, 2024)
Soil washing is one of the effective methods to remove contaminants in polluted soil by moving them from the solid phase (soil) to the liquid phase (water). This study examines the effect of soil washing on the concentration of Total Petroleum Hydrocarbon (TPH) in petroleum-polluted soil at the Ex-Mining Area in Jambi and the removal of oil and grease in soil washing residue using a fixed bed column. The soil washing method uses a leaching column with various concentrations of Tween 80 surfactant solution of 0.5% (v/v) and 1% (v/v). In addition, leaching was repeated 0, 1, and 2 times. Coffee husk biochar was used as a medium in a fixed bed column to remove oil and grease from soil-washing residue with thickness variations of 10 cm, 20 cm, and 30 cm. The results showed that the soil was loamy sand with an initial TPH content of 3092.75 mg/kg. The soil-washing process reduced the TPH concentration with a removal efficiency of 72.45-90.40%. The highest TPH removal occurred in one leaching repetition at a 0.5% surfactant concentration. The optimum oil and fat removal from the use of a fixed bed column is at 30 cm thickness which is 94.35%.